2015
DOI: 10.1016/j.bbmt.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Donor Lymphocyte Infusions for Chronic Myeloid Leukemia Relapsing after Allogeneic Stem Cell Transplantation: May We Predict Graft-versus-Leukemia Without Graft-versus-Host Disease?

Abstract: Donor lymphocyte infusions (DLI) are an effective treatment for relapsed chronic myeloid leukemia (CML) after allogeneic stem cell transplantation (alloSCT). Leukemia resistance and secondary graft-versus-host disease (GVHD) are major obstacles to success with DLI. The aim of this study was to identify pre-DLI factors associated with prolonged survival in remission without secondary GVHD. We retrospectively analyzed 500 patients treated with DLI for CML relapse (16% molecular, 30% cytogenetic, and 54% hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…These results have been collected by the European group for Blood and Marrow Transplantation (EBMT) (29), the US (26), and Japanese transplant centers (30). The best results with 70–80% cytogenetic complete remissions were reported for CML in cytogenetic and hematological relapse, other important factors being the presence of chronic GvHD prior to DLI and the time of relapse post-HSCT (31). Donor chimerism was also necessary for a successful GvL in CML.…”
Section: Clinical Results Using DLI For Relapse After Hematopoietic Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have been collected by the European group for Blood and Marrow Transplantation (EBMT) (29), the US (26), and Japanese transplant centers (30). The best results with 70–80% cytogenetic complete remissions were reported for CML in cytogenetic and hematological relapse, other important factors being the presence of chronic GvHD prior to DLI and the time of relapse post-HSCT (31). Donor chimerism was also necessary for a successful GvL in CML.…”
Section: Clinical Results Using DLI For Relapse After Hematopoietic Cmentioning
confidence: 99%
“…CML relapse, molecular cytogenetic, or hematological has been reported as ranging from 16, 30, and 54%, respectively, using data from the Chronic Malignancies Working Party for the EBMT and based on 500 HSCT transplants from 1968 to 2004. The use of DLI in these cases was most successful if pre DLI factors such as chronic GvHD, cell dose, patient and donor gender mismatch, as previously described was taken into account (31). …”
Section: Prophylactic and Preemptive DLImentioning
confidence: 99%
“…Although the small sample size of our cohorts limited a reliable comparison, it is noteworthy that all patients with GVHD received DLI within the first year after alloSCT as compared with only 2 of 6 patients without GVHD. It was shown that the probability to survive without GVHD was highest if DLI was given 1 year or more after alloSCT (32,33). Early after alloSCT, higher levels of residual patient APCs may elicit higher response magnitudes.…”
Section: Expression Of Miha-encoding Genesmentioning
confidence: 99%
“…Responses achieved after DLI are frequently durable, offering a potential cure for the majority of patients. 35 , 36 After effective therapy with DLI, CHR and CCyR were detected. Then, the patient received therapy with dasatinib (100 mg daily).…”
Section: Discussionmentioning
confidence: 97%